2012
DOI: 10.1177/0886260512455867
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence in India

Abstract: This article assesses the prevalence and risk factors of domestic violence in India. The study uses the 2005-2006 India National Family Health Survey-III (NFHS-III) and focuses on the 69,484 ever-married women ages 15 to 49 from all regions, who were administered the domestic violence module. The results show that 31% of respondents experienced physical violence in the past 12 months before the survey; the corresponding figure for sexual violence was 8.3%. The multivariate logistic regression results show key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 34 publications
4
60
1
Order By: Relevance
“…In South Asia gender roles are rigid and there are widespread, deep-rooted patriarchal values that emphasise male authority in several aspects of everyday life. Patriarchal culture enforces male dominance and entitlement to control [18] and violence is used to control female obedience [19] and to disciplining women [20]. In many parts of South Asia the police force, legal departments and health sectors are permeated with patriarchal norms and values, which make help-seeking difficult for women [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Asia gender roles are rigid and there are widespread, deep-rooted patriarchal values that emphasise male authority in several aspects of everyday life. Patriarchal culture enforces male dominance and entitlement to control [18] and violence is used to control female obedience [19] and to disciplining women [20]. In many parts of South Asia the police force, legal departments and health sectors are permeated with patriarchal norms and values, which make help-seeking difficult for women [18].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to 1983, India did not have any legal regulations on violence within marriage [19]. The Protection of Women from Domestic Violence Act (PWDVA) was passed in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, female students tend to have a higher level of awareness of violence against women than male students (Agrawal & Banerjee, 2010). Social and cultural norms, in which younger women have less power than male or older female family members within a family, are closely related to violence against women (Kamimura, Nourian, Assasnik, Rathi, & Franchek-Roa, 2016;Kimuna, Djamba, Ciciurkaite, & Cherukuri, 2013).…”
Section: Indiamentioning
confidence: 99%
“…The results of this study suggest women utilizing community health centers reported not only high prevalence of abuse experience but also multiple perpetrators (parents/other adults, spouse, in-laws) and types of abuse (physical, sexual, and emotional abuse). The prevalence of physical and sexual abuse among the participants was higher than the national average (Kimuna et al, 2013). Health care providers should assess each type of abuse and take an active role to deal with patients with multiple types of abuse, which can significantly affect their health (Fanslow & Robinson, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Violence against women in India is closely related to social and cultural norms and the notion of power dynamics in a family (Kimuna, Djamba, Ciciurkaite, & Cherukuri, 2013). Examining multiple types of family violence, not just one type of family violence, may better describe culture or power dynamics that cause violence against women.…”
Section: Introductionmentioning
confidence: 99%